Towards a parallel exceptional welfare system: the scaling down and out of forced migrants' reception in Italy. Issue 7 (9th August 2021) - Semprebon, Michela
ABSTRACT: Reception measures have been implemented in many EU countries, as part of an articulated framework of European, national, subnational, local normative arrangements. This paper states the need for more attention on the division of responsibility among government levels and forms of contention associated with it, moving beyond the Scholten's framework (2013) focused on actors' coordination. In doing so, it argues that an increased focus on the welfare perspective can illuminate how a parallel, exceptional system of welfare has been created and consolidated ad hoc  for forced migrants, with potentially negative impacts on their social protection. The argument builds on empirical evidence collected in Italy in the period 2014-2020. Beyond the specificity of the Italian case, the paper aims to put forward a more general discussion on how the literature on welfare can provide a useful theoretical background to analyse the relationship between forced migrants and the city.